Failure to initiate HIV treatment in patients with high CD4 counts: evidence from demographic surveillance in rural South Africa - Bor, Jacob; Chiu, Calvin; Ahmed, Shahira; Katz, Ingrid; Fox, Matthew P.; Rosen, Sydney; Yapa, Manisha; Tanser, Frank; Pillay, Deenan; Bärnighausen, Till (Tropical medicine & international health, 2018)
Objectives: To assess the relationship between CD4 count at presentation and ART uptake and assess predictors of timely treatment initiation in rural KwaZulu-Natal, South Africa. Methods: We used Kaplan-Meier and Cox proportional hazards models to assess the association between first CD4 count and time from first CD4 to ART initiation among all adults presenting to the Hlabisa HIV Treatment and Care Programme between August 2011 and December 2012 with treatment-eligible CD4 counts (≤ 350 cells/mm3). For a subset of healthier patients (200 < CD4 ≤ 350 cells) residing within the population surveillance of the Africa Health Research Institute, we assessed sociodemographic, economic and geographic predictors hypothesised to influence ART uptake. Results: A total of 4739 patients presented for care with eligible CD4 counts. The proportion initiating ART within six months of diagnosis was 67% (95% CI 63, 71) in patients with CD4 ≤ 50, 59% (0.55, 0.63) in patients with CD4 151-200 and 48% (95% CI 44, 51) in patients with CD4 301-350. The hazard of starting ART fell by 17% (95% CI 14, 20) for every 100-cell increase in baseline CD4 count. Among healthier patients under demographic surveillance (n = 193), observable sociodemographic, economic and geographic predictors did not add discriminatory power beyond CD4 count, age and sex to identify patients at high risk of non-initiation. Conclusions: Individuals presenting for HIV care at higher CD4 counts were less likely to initiate ART than patients presenting at low CD4 counts. Overall, ART uptake was low. Under new guidelines that establish ART eligibility regardless of CD4 count, patients with high CD4 counts may require additional interventions to encourage treatment initiation.
First published: 21 November 2017
Gesehen am 02.04.2020